Using Debate to Promote Students’ Reflective Understanding of Research Ethics - Monica Eviandaru Madyaningrum (Universitas Ahmad Dahlan, 2022)
This article reported a qualitative study that examined the use of debate to promote students’ reflective understanding of research ethics. The study was conducted in a qualitative methodology class for undergraduate students in psychology. Data were collected from 36 students attending the class by using an open-ended questionnaire. There were four questions in the questionnaire which were intended to gauge students’ understanding of ethical issues in qualitative research. The questionnaire was distributed twice, before and after the students engaged in the debate. During the debate, the students had to argue about dilemmatic research situations that reflected ethical issues in research. Thematic analysis was used to qualitatively examine and compare the students’ responses, before and after the debate. The findings suggested four themes that represented a shift in the students’ understanding of research ethics. These themes indicated the emergence of more contextual and reflective views of research ethics among the students.